Nonlinear response and threshold regulation of agroforestry ecosystem quality to morphological characteristics in karst desertification habitats - Zhigao Wu; Xingfu Wang; Xiaojun Wang; Jie Xiao; Yiling Yang; Xuntong Zhuang; Jia Ma (Ecological Indicators)
Agroforestry is a primary ecological restoration measure in karst desertification (KD) areas and provides important ecological services to effectively curb ecosystem degradation and promote recovery. However, improving the quality level effectively, which is key to maintaining the sustainable supply capacity of agroforestry ecosystems (AFSs), has become a new challenge. To elucidate the driving mechanisms underlying AFS quality enhancement in KD regions, three representative KD habitats, namely, none-potential (N-P), potential-slight (P-S) and medium-intensity (M−I) habitats, were selected as samples in this study. In accordance with the theory of spatial morphology, this study proposes an external pattern optimization method based on morphological features, reveals the spatial response of the quality of AFSs to their morphological features, and elucidates the key morphological factors and optimal regulatory thresholds. The results revealed that among the different KD habitat types, the agroforestry morphology composite index and the level of ecosystem quality in the P-S habitat were significantly better than those in the N-P and M−I habitats. The spatial correlation characteristics revealed significant positive correlations between the quality and morphological characteristics of AFSs in all habitats, indicating a coordinated dynamic change relationship. However, the spatial response dynamics of the two habitats exhibited nonlinear threshold effects, and the correlation process was characterized by phases. The indicator LPI had a key influence on the quality enhancement of AFSs in N-P and M−I habitats, with regulation thresholds of 38.7 % < LPI < 78.9 % and LPI < 18.4 %, respectively. The indicator COHESION was a key influencing factor in P-S habitats, with a regulatory threshold of COHESION > 31.6 %. Given the unique KD habitats, blindly increasing the area of agroforestry cultivation would not only be inefficient but also introduce additional ecological risks. Optimizing agroforestry forms according to local conditions is the key to improving the quality of existing stocks. The results of this study suggest a variety of morphology optimization strategies for different KD habitats, which will help continuously exploit the multifunctional value of AFSs and provide scientific paths for consolidating and expanding the effectiveness of KD control.